THE IMPLEMENTATION OF TEXT-BASED TASK IN LANGUAGE LEARNING IN IMPROVING THE STUDENTS’ WRITING SKILL AND CREATIVITY - St. Shabriani (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research aimed to find out 1) whether or not the use of text-based tasks in language learning improved students’ writing skill and 2) whether or not the use of text-based task in writing increased students’ creativity in terms of fluency, flexibility, and originality. This research employed quasi-experimental design with two groups; control and experimental. It used pre-test and post-test as the instruments of the research for both tests: writing test and creativity test. In treatment, experimental group was taught by applying text-based task whereas control group was conventional method; three phases technique. The result of data analysis showed that the use of text-based task in language learning improved students’ writing skill. It can be seen from the mean score, standard deviation, and scoring classification of experimental group which are improved significantly and also from the component of writing where scores of content, organization, language use, and mechanics of students in experimental group are higher than control group. The t-test value of writing in posttest was 3.895 ≥ t-table 2.000; it means that the alternative hypothesis is accepted. Text-based task improved students’ writing. The result also showed that students’ ability to produce number of category of ideas (flexibility) and produce new idea (originality) as part of creativity improved significantly through text-based task whereas the number of ideas (fluency) did not show significant improvement.